The Effectiveness of Blooket Media Toward Student’s Vocabulary Mastery - Sulistyanto, Irwan; Asyhar, Wildan Isna (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The purpose of this study is to determine whether Blooket media is effective in teaching vocabulary and to discover about students' perceptions of the usage of Blooket media in teaching vocabulary. This research approach is quantitative with quasi-experimental as the design. Students are divided into two groups with 20 students in each group. In both pre- and post-test, data was collected using 20 multiple-choice questions. To know the student’s perception about the use of Blooket, 11 items of questionnaires was utilized. The research results showed that Blooket media is effective for increasing the students’ vocabulary mastery. Furthermore, students at experimental group were positively respond to the use of Blooket media.